2008
DOI: 10.5194/bgd-5-3699-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Greenhouse gas emissions (CO<sub>2</sub>, CH<sub>4</sub> and N<sub>2</sub>O) from perialpine and alpine hydropower reservoirs

Abstract: Abstract. In eleven reservoirs located at different altitudes in Switzerland depth profiles of greenhouse gas (CO2, CH4, and N2O) concentrations were measured several times during spring and summer. Trace gas emissions were calculated using surface concentrations, wind speeds and transfer velocities. Additionally we assessed methane loss at the turbine and the methane input by inflowing water. All reservoirs were net emitters of CO2 with an average of 1030±780 mg m−2 d−1 and of methane with an average of 0.20±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Our studies over the last 5 years showed that almost all of the investigated lakes and reservoirs in Switzerland are a source for methane (Diem et al 2008). Similarly for Lake Rotsee, we show that, although most of the methane is oxidized during its way through the water column, the lake surface is still oversaturated in methane compared to the atmosphere and serves as a source of methane.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our studies over the last 5 years showed that almost all of the investigated lakes and reservoirs in Switzerland are a source for methane (Diem et al 2008). Similarly for Lake Rotsee, we show that, although most of the methane is oxidized during its way through the water column, the lake surface is still oversaturated in methane compared to the atmosphere and serves as a source of methane.…”
Section: Introductionsupporting
confidence: 66%
“…They were at minimum 40 times higher (February, 80 nM) and up to 600 times higher in November (1,200 nM), demonstrating that the surface water of Lake Rotsee was always oversaturated and, therefore, a source of methane to the atmosphere. This holds true for all lakes and reservoirs in Switzerland that we have investigated over the last 5 years (Diem et al 2008). Methane emission values calculated from the boundary layer model using the formula by Cole and Caraco (1998) were two times higher than values derived using the formula from Crusius and Wanninkhof (2003) in November (Table 2).…”
Section: Surface Water Methane Concentrations and Methane Emissionsmentioning
confidence: 60%